Effects of Structural Integrity on Improving the Resistance to Dynamic Loads - Emilia Juhasova (Communications - Scientific letters of the University of Zilina, 2007)
The paper deals with the approaches to the dynamic response analysis when non-linear response of the structure including its partial damage is expected. This concerns the building and other structures executed near transport lines and possibly subjected to seismic effects from transport or earthquakes. Seismic response is here analysed under the action of near field earthquake that was considered and applied as 6DOF seismic input and 2DOF seismic input. A typical reinforced concrete frame with masonry infills was chosen as the prototype for the experimental tests and next analysis. Two storey one bay 1:1 model was tested on a large shaking table with sequentially increasing intensity of seismic input. The specimen was designed according to the rules of Eurocode 8 and the masonry infill was strengthened with horizontal polymer grids placed in prescribed bed joints. The non-linear behaviour is analysed in view of pushover analysis approach and limits of interstorey drift. General behaviour of the analysed frame showed reasonable seismic resistance that was supported by sufficient integrity and limited cracks appearance.